Multiple Evolutionary Events Involved in Maintaining Homologs of Resistance to Powdery Mildew 8 in Brassica napus - Li, Qin; Li, Jing; Sun, Jin-Long; Ma, Xian-Feng; Wang, Ting-Ting; Berkey, Robert; Yang, Hui; Niu, Ying-Ze; Fan, Jing; Li, Yan; Xiao, Shunyuan; Wang, Wen-Ming (Frontiers in Plant Science, 2016)
The Resistance to Powdery Mildew 8 (RPW8) locus confers broad-spectrum resistance to powdery mildew in Arabidopsis thaliana. There are four Homologous to RPW8s (BrHRs) in Brassica rapa and three in B. oleracea (BoHRs). B. napus (Bn) is derived from diploidization of a hybrid between B. rapa and B. oleracea, thus should have seven homologs of RPW8 (BnHRs). It is unclear whether these genes are still maintained or lost in B. napus after diploidization and how they might have been evolved. Here we reported the identification and sequence polymorphisms of BnHRs from a set of B. napus accessions. Our data indicated that while the BoHR copy from B. oleracea is highly conserved, the BrHR copy from B. rapa is relatively variable in the B. napus genome owing to multiple evolutionary events, such as gene loss, point mutation, insertion, deletion and intragenic recombination. Given the overall high sequence homology of BnHR genes, it is not surprising that both intragenic recombination between two orthologs and two paralogs were detected in B. napus, which may explain the loss of BoHR genes in some B. napus accessions. When ectopically expressed in Arabidopsis, a C-terminally truncated version of BnHRa and BnHRb, as well as the full length BnHRd fused with YFP at their C-termini could trigger cell death in the absence of pathogens and enhanced resistance to powdery mildew disease. Moreover, subcellular localization analysis showed that both BnHRa-YFP and BnHRb-YFP were mainly localized to the extra-haustorial membrane (EHM) encasing the haustorium of powdery mildew. Taken together, our data suggest that the duplicated BnHR genes might have been subjected to differential selection and at least some may play a role in defense and could serve as resistance resource in engineering disease-resistant plants.